1975
DOI: 10.1111/1523-1747.ep12607630
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes In The Resident Bacterial Flora Of The Human Face

Abstract: Quantitative levels of resident aerobic and anaerobic bacteria of the face, show a characteristic age-related pattern. The density of anaerobic diptheroids and surface aerobic micrococci is higher in infancy than in early childhood. At puberty the quantity of organisms increases, with significantly higher levels achieved in late adolescence. Maximum counts are attained in early adulthood and remain constant until old age when a trend toward lower numbers occurs. These changes seem to correlate with the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(112 citation statements)
references
References 7 publications
12
96
0
Order By: Relevance
“…However, in our study, when the same strains of Micrococcaceae were tested against strains of P. acnes as indicators of inhibitory activity, the frequency rose to 9.5%. Because P. acnes outnumbers Micrococcaceae on the skin by about ten to one (Leyden et al, 1975;Puhvel, Reisner and Amirian, 1975) the production of inhibitors of P. acnes may be of survival advantage to the Micrococcaceae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in our study, when the same strains of Micrococcaceae were tested against strains of P. acnes as indicators of inhibitory activity, the frequency rose to 9.5%. Because P. acnes outnumbers Micrococcaceae on the skin by about ten to one (Leyden et al, 1975;Puhvel, Reisner and Amirian, 1975) the production of inhibitors of P. acnes may be of survival advantage to the Micrococcaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Propionibacterium acnes (Corynebacterium acnes) which for many years since its first isolation (Sabouraud, 1897) has been considered the likeliest pathogen, co-exists on normal skin, in healthy sebaceous follicles and in acne lesions with members of the Micrococcaceae, particularly Staphylococcus epidermidis biotype 1 (Baird-Parker, 1974), and with the yeast Pityrosporum ovule. This subject was well reviewed by Rosenberg (1969) and by Marples (1974). The production of inflammatory lesions when P .…”
Section: Plate I11mentioning
confidence: 99%
See 1 more Smart Citation
“…Actinobacteria (52%), Firmicutes (24%), Proteobacteria (17%) and Bacteroidetes (7%) are the four most abundant species identified on the skin 8. Previous studies have shown that it is not only skin topography that influences microbial colonization, but also a vast range of host‐specific factors including age and sex, and environmental factors such as occupation, clothing choice, antibiotic use, cosmetics, soaps, environmental temperature, humidity, and longitudinal and/or latitudinal variation in UV exposure, which can all contribute to the variability seen in the microbial flora of the skin 9, 10, 11, 12, 13, 14, 15. Moreover, changes or aberrations in the skin microbiome have been implicated in the pathophysiology of numerous skin diseases such as AD and AV 16.…”
Section: Introductionmentioning
confidence: 99%
“…appeared to be the causative agent. [12] Treatment of acne vulgaris often includes combinations of oral and topical agents such as antimicrobials, retinoids, and hormonal agents. Laser and light sources are additional treatment options.…”
Section: Discussionmentioning
confidence: 99%